First-principles determination of the mechanical and physical properties of Ag alloyed α-ZrSi based on the density functional theory. (December 2020) - Cheng, Lang; Xu, Jiang; Zhang, Yuechao; Zhao, Yanjie; Peng, Shuang; Jiang, Shuyun; Lu, Hong
Graphical abstract: Highlights: It is a computational study on the effects of Ag additions to α-ZrSi(1-x) Agx . Ag additions improved the toughness of α-ZrSi(1-x) Agx . Ag additions optimized the thermal expansion and sound velocities anisotropy. The optimal combination of ductility and stability is obtained when x = 0.1875. The changes of above properties were discussed through the electronic structure. Abstract: By using first-principles density functional theory calculations, the effects of silver additions to the structure, mechanical properties, and physical properties of α-ZrSi were systematically calculated. This modeling indicated that the Ag atoms preferentially replace Si 4c atoms, and α-ZrSi(1-x) Agx changes from a brittle to ductile material when the concentration of Ag reaches x = 0.1875. With increasing Ag concentration, the modulus anisotropy of α-ZrSi(1-x) Agx increased slightly, while the toughness is significantly improved and the thermal expansion anisotropy is optimized. Further, the sound velocity anisotropy and Debye temperature of α-ZrSi(1-x) Agx were also studied. Finally, the changes in the above properties were discussed through a consideration of the electronic structure of these compounds.